2014
DOI: 10.3126/kumj.v10i4.10995
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Prevalence of Helicobacter Pylori in Patients with Acne Rosacea

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
(26 reference statements)
0
14
0
1
Order By: Relevance
“…Fourteen studies were included in the final analysis, including a total of 928 rosacea patients and 1527 controls. All studies were published between 1998 and 2015; six were from Southern Europe, two from Northern Europe, two from the United States, and one study from Egypt, Nepal, Korea and Brazil, respectively. Seven of the included studies also examined the effect of therapy on rosacea‐related skin symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies were included in the final analysis, including a total of 928 rosacea patients and 1527 controls. All studies were published between 1998 and 2015; six were from Southern Europe, two from Northern Europe, two from the United States, and one study from Egypt, Nepal, Korea and Brazil, respectively. Seven of the included studies also examined the effect of therapy on rosacea‐related skin symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14] The role of Helicobacter pylori-related gastritis in the pathogenesis of rosacea has also been a subject of controversy. Diverse prevalence of H. pylori infection has been reported among rosacea patients, [15][16][17][18][19][20][21] ranging 0-100%. Some studies have suggested that rosacea could be considered as an extra-gastric symptom of H. pylori infection or reported improved rosacea clinical course post-H. pylori eradication, 22,23 while others concluded no significant relationship between H. pylori infection and rosacea.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors suggest a causal relationship between the two disorders, based on the RS clinical improvement after HP treatment (2,3,4,5) and the high incidence of this microorganism in RS patients (6,7). Improvment in the symptomatology of the disease noticed after the treatment of HP infection is supported by several studies, while other authors consider that this treatment and RS evolution are not connected (8,9).…”
Section: Results Resultsmentioning
confidence: 95%